The relationship between unwanted sexual experiences, psychological well-being, substance abuse and high-risk sexual behaviour among adolescent - Visser, M.J. (Maretha Johanna) (University of Pretoria, 2013)
Dissertation (MA (Clinical Psychology))--University of Pretoria, 2007.